Instruments of darkness eaudiobook A novel. - Robertson, Imogen (Tantor Media, 2011)
In the year 1780, Harriet Westerman, the willful mistress of a country manor in Sussex, finds a dead man on her grounds with a ring bearing the crest of Thornleigh Hall in his pocket. Not one to be bound by convention or to shy away from adventure, she recruits a reclusive local anatomist named Gabriel Crowther to help her find the murderer, and historical suspense's newest investigative duo is born. For years, Mrs. Westerman has sensed the menace of neighboring Thornleigh Hall, seat of the Earl of Sussex. It is the home of a once-great family that has been reduced to an ailing invalid, his whorish wife, and his alcoholic second son, a man haunted by his years spent as a redcoat in the Revolutionary War. The same day, Alexander Adams is slain by an unknown killer in his London music shop, leaving his children orphaned. His death will lead back to Sussex and to an explosive secret that has already destroyed one family and threatens many others. Instruments of Darkness combines the brooding atmosphere of Anne Perry with the complex, compelling detail of Tess Gerritsen, moving from drawing room to dissecting room, from coffee house to country inn. Mrs. Westerman and Mr. Crowther are both razor-sharp minds, and their personalities breathe spirit into this gripping historical mystery.